Metode Cerita dan Menyanyi sebagai Pembelajaran Ibadah Amaliyah di TPA Al Barokah Siman Ponorogo - Kurniawan, Bekti Galih; Muslih, Mohammad Kholid; Al Manaanu, Yusuf; Tifani, M. Akhlis Azamuddin; Arif, Achmad (Penerbit Widina, Widina Media Utama, 2025)
The proficiency in practical worship (ibadah amaliyah) encompasses the understanding and implementation of worship according to the teachings of the Qur'an and Hadith. In practice, this method faces several challenges, such as difficulties in crafting relevant story materials, effectively combining storytelling and singing, and addressing the varying abilities of children to understand and memorize worship content. This community service is carried out through partner analysis, socialization, and the implementation of activities in three stages (preparation, core implementation, and evaluation), followed by program evaluation. The results indicate that the storytelling and singing method is effective in enhancing children's understanding and memorization of prayers and worship procedures. The children became more enthusiastic and focused during the lessons, and they were able to better memorize prayers and understand the steps of worship. The program evaluation also revealed positive impacts on teaching in TPA (Taman Pendidikan Al-Qur'an), as well as increased motivation for children to perform worship at home. This community service contributes to the development of enjoyable and effective religious learning methods that can be applied in other TPAs to improve children's proficiency in practical worship.ABSTRAKKecakapan ibadah amaliyah meliputi pemahaman dan pelaksanaan ibadah sesuai dengan ajaran Al-Qur'an dan Hadis. Dalam praktiknya, metode ini menghadapi beberapa tantangan, seperti kesulitan dalam menyusun materi cerita yang relevan, mengkombinasikan cerita dan menyanyi secara efektif, serta mengatasi perbedaan kemampuan anak dalam memahami dan menghafal materi ibadah. Pengabdian ini dilaksanakan melalui analisis mitra, sosialisasi, pelaksanaan kegiatan dalam tiga tahap (persiapan, pelaksanaan inti, dan evaluasi), serta evaluasi program. Hasilnya menunjukkan bahwa metode cerita dan menyanyi efektif dalam meningkatkan pemahaman dan hafalan doa serta tata cara ibadah pada anak-anak. Anak-anak menjadi lebih antusias dan fokus selama pembelajaran, dan mereka dapat menghafal doa serta mengerti langkah-langkah ibadah dengan lebih baik. Evaluasi program juga mengungkapkan dampak positif terhadap pengajaran di TPA, serta peningkatan motivasi anak untuk beribadah di rumah. Pengabdian masyarakat ini memberikan kontribusi dalam pengembangan metode pembelajaran agama yang menyenangkan dan efektif, yang dapat diterapkan di TPA lain untuk meningkatkan kecakapan ibadah amaliyah anak-anak.